Macrolide Antibiotics and Survival in Patients With Acute Lung Injury - Walkey, Allan J. (American College of Chest Physicians, 2012)
BACKGROUND: Animal models suggest that immunomodulatory properties of macrolide antibiotics have therapeutic value for patients with acute lung injury (ALI). We investigated the association between receipt of macrolide antibiotics and clinical outcomes in patients with ALI. METHODS: Secondary analysis of multicenter, randomized controlled trial data from the Acute Respiratory Distress Syndrome Network Lisofylline and Respiratory Management of Acute Lung Injury Trial, which collected detailed data regarding antibiotic use among participants with ALI. RESULTS: Forty-seven of 235 participants (20%) received a macrolide antibiotic within 24 h of trial enrollment. Among patients who received a macrolide, erythromycin was the most common (57%), followed by azithromycin (40%). The median duration of macrolide use after study enrollment was 4 days (interquartile range, 2-8 days). Eleven of the 47 (23%) patients who received macrolides died, compared with 67 of the 188 (36%) who did not receive a macrolide (P = .11). Participants administered macrolides were more likely to have pneumonia as an ALI risk factor, were less likely to have nonpulmonary sepsis or to be randomized to low tidal volume ventilation, and had a shorter length of stay prior to trial enrollment. After adjusting for potentially confounding covariates, use of macrolide was associated with lower 180-day mortality (hazard ratio [HR], 0.46; 95% CI, 0.23-0.92; P = .028) and shorter time to successful discontinuation of mechanical ventilation (HR, 1.93; 95% CI, 1.18-3.17; P = .009). In contrast, fluoroquinolone (n = 90) and cephalosporin antibiotics (n = 93) were not associated with improved outcomes. CONCLUSIONS: Receipt of macrolide antibiotics was associated with improved outcomes in patients with ALI.